Financial Intermediation, Moral Hazard, And Pareto Inferior Trade - Bodil Olai Hansen; Hans Keiding (Copenhagen Business School (CBS), Department of Economics, 2006)
We consider a simple model of international trade under uncertainty, where production takes time and is subject to uncertainty. The riskiness of production depends on the choices of the producers, not observable to the general public, and these choices are influenced by the availability and cost of credit. If investment is financed by a bond market, then a situation may arise where otherwise identical countries end up with different levels of interest and different choices of technique, which again implies differences in achieved level of welfare. Under suitable conditions on the parameters of the model, the market may not be able to supply credits to one of the countries. The introduction of financial intermediaries with the ability to control the debtors may change this situation in a direction which is welfare improving (in a suitable sense) by increasing expected output in the country with high interest rates, while opening up for new problems of asymmetric information with respect to the monitoring activity of the banks.
hdl:10398/7498
Keywords: D92; E44; F36; 330; Capital outflow; financial intermediaries; moral hazard